SIDEROPHORES AND THE DISSOLUTION OF IRON-BEARING MINERALS IN MARINE SYSTEMS - Kraemer S.M.; Butler A.; Borer P.; Cervini-Silva J. (My University, 2005)
Metal ions have critical functions in biological processes and provided important biological feedbacks with the environment throughout earth history. For example, Fe, Ni, Mg, Mn, Mo, Cu, W, V, and Zn play an essential role as catalysts in key compounds involved in respiration, photosynthesis, nitrogen fixation, and many other enzymatic processes.
Keywords: metal ions; dissolution; marine systems